Martin S. Gilderman, Juan Rodríguez de la Cámara. Twayne, Boston G. K. Hall & Co., 1977; 152 pp. (Twayne's world authors, 432). - Tudorica Impey, Olga (El Colegio de México, 1979)
Se reseñó el libro: Juan Rodríguez de la Cámara.